Ta có \left\{ \begin{array}{l} x^2+2y^2-3x+2xy=0 (1)\\ xy(x+y)+(x-1)^2=3y(1-y) (2) \end{array} \right.Lấy $(1)-(2)=xy(x+y)+x+y^2-2xy-3y+1=0\Leftrightarrow y^2+xy-3xy-3y+xy(x+y)+x+1=0\Leftrightarrow (x+y)(xy+y)-3y(x+1)+(x+1)=0\Leftrightarrow (x+1)(y^2-3y+xy+1)=0*TH1: x=-1Thế vào (1) \Rightarrow y^2-y+2=0 (vô nghiệm)*TH2: y^2-3y+xy+1=0Nhận xét: y=0 \Rightarrow pt vô nghiệmy\neq 0 \Rightarrow x=-y-\frac{1}y +3Thế vào (1) \Rightarrow y^2+\frac{1}{y^2}+3(y-\frac{1}y)=0Đặt t=y-\frac{1}y \Rightarrow t^2+3t+2=0$Giải t ra, rồi giải x sẽ có được kết quả rồi bạn ạ
Ta có
\left\{ \begin{array}{l} x^2+2y^2-3x+2xy=0 (1)\\ xy(x+y)+(x-1)^2=3y(1-y) (2) \end{array} \right.Lấy $(
2)-(
1)=xy(x+y)+x+y^2-2xy-3y+1=0
\Leftrightarrow y^2+xy-3xy-3y+xy(x+y)+x+1=0\Leftrightarrow (x+y)(xy+y)-3y(x+1)+(x+1)=0
\Leftrightarrow (x+1)(y^2-3y+xy+1)=0*TH1: x=-1
Thế vào (1) \Rightarrow y^2-y+2=0
(vô nghiệm)*TH2: y^2-3y+xy+1=0
Nhận xét: y=0 \Rightarrow
pt vô nghiệmy\neq 0 \Rightarrow x=-y-\frac{1}y +3
Thế vào (1) \Rightarrow y^2+\frac{1}{y^2}+3(y-\frac{1}y)=0
Đặt t=y-\frac{1}y \Rightarrow t^2+3t+2=0$Giải t ra, rồi giải x sẽ có được kết quả rồi bạn ạ